Surgical anatomy of cervical sympathetic trunk: a cadaveric study - Manuel, Nimmy; S., Lekha K.; Das, Lola; N., Seena (International Journal of Research in Medical Sciences, 2022)
Background: Cervical sympathetic trunk (CST) is at risk of injury during surgical procedures of cervical spine and may result in Horner’s syndrome. The purpose of present study was to clearly describe the surgical anatomy of CST with respect to the surrounding structures and to analyse the anatomical variations. Methods: In this cross-sectional study, 50 cervical sympathetic chains were studied by bilateral neck dissections of 25 formalin fixed human cadavers from the Department of Anatomy, Government medical college Thrissur. Results: Cervical sympathetic chain was found inside the carotid sheath in 1 (2%) side of neck. Superior cervical ganglion (SCG) was consistently seen in all sympathetic chains. Middle cervical ganglion (MCG) was present in 27 (54%) chains studied; vertebral ganglion (VG) was present in 33 (66%) chains. Inferior cervical ganglion (ICG) was present in 38 (76%) CSTs. In case of stellate ganglion (SG), it was present in 12 (24%) chains. The most common type of CST was type 1 consisting of SCG, VG and ICG (17, 34%). Out of 25 cadavers studied, sympathetic chain appeared similar on right and left sides in 14 cadavers. Conclusions: This study concludes that variations occur in cervical sympathetic chain with regard to occurrence and measurements of its ganglia. Our study also emphasizes the need for awareness of the CST’s anatomy during cervical surgical procedures to prevent inadvertent injury to it.